Social Media And The Practice Of Public Relations In Mass Media Organizations (Eurasian Journal of Media and Communications, 2024)
The integration of social media platforms has redefined how mass media organizations communicate with their audiences. This paradigm shift goes beyond mere dissemination, embracing a two-way symmetrical communication model where organizations actively engage with their audience. Social media serves as a real-time conduit for disseminating news, responding to queries, and fostering meaningful dialogues.Traditionally adept at setting the agenda, mass media organizations extend their influence through strategic use of social media. By curating content, emphasizing specific narratives, and participating in trending discussions, these entities actively shape public discourse and influence the issues that capture the attention of the audience. The real-time nature of social media has altered the landscape of crisis communication. Mass media organizations now navigate through the challenges of managing crises in the digital realm, where information spreads rapidly. Social media serves as a powerful tool for mitigating reputational damage, correcting misinformation, and providing timely updates during critical situations.Despite its advantages, the integration of social media into PR practices brings forth challenges. Information overload, privacy concerns, and the rapid dissemination of misinformation pose intricate hurdles. Mass media organizations grapple with the need for instant responsiveness while ensuring accuracy and reliability in the information they share.Strategies employed by mass media organizations encompass the spectrum of PR practices